OS5.3 Imaging comparative analysis of intracranial meningiomas in adult and pediatric NF2 patients. (19th September 2018) - Li, P; Yang, Z; Wang, Z; Wang, X; Wang, B; Liu, P
Abstract: Background: Various central nervous system tumors show different clinical behaviors in adult and pediatric patients. Intracranial meningiomas are the main cause of neurofibromatosis type 2 (NF2) patients' death. It is very important to know well of the detailed clinical behaviors of the death-cause NF2 intracranial meningiomas. It will help us to make up optimal treatment strategy for every single NF2 patient. The aim of this study is to evaluate the differences in the clinical behaviors of intracranial meningiomas in adult and pediatric NF2 patients via analyzing the MR imaging data. Material and Methods: The study was a retrospective review of 452 NF2 patients. Their cranial MR imaging data were carefully reviewed. The location patterns of meningiomas in adult and pediatric patients were calculated and compared with each other. Results: The total 452 NF2 patients included 367 adult and 85 pediatric (younger than 18 years old) patients. Twenty five adult NF2 patients had more than 10 intracranial meningiomas, and they were defined as severe-type NF2 in our study. To avoid selection bias, they were excluded from the comparative analysis. None pediatric patients had more than 10 intracranial meningiomas. Of the remaining no-severe-type 342 adult patients, 216 patients had 629 meningiomas and 126 patients had none. Of the total 85 pediatric patients, 50 patients had 81 meningiomas and 35 patients had none. The locations of adult and pediatric meningiomas included parafalcine (28.9% vs. 29.6%), parasagittal (15.4% vs. 6.2%), convex surface (22.3% vs. 14.8%), tentorial (6.0% vs. 7.4%), anterior cranial fossa (4.9% vs. 6.2%), middle cranial fossa (5.7% vs. 11.1%), posterior cranial fossa (9.4% vs. 8.6%), intraorbital (1.4% vs. 3.7%), lateral ventricle (5.9% vs. 12.4%). The 25 severe-type adult patients were analyzed separately. They had 310 intracranial meningiomas. Their locations included parafalcine (25.2%), parasagittal (20.0%), convex surface (31.0%), tentorial (8.4%), anterior cranial fossa (2.9%), middle cranial fossa (4.8%), posterior cranial fossa (2.9%), intraorbital (0.7%), lateral ventricle (4.2%). Conclusion: The location patterns of intracranial meningiomas vary in adult and pediatric NF2 patients. The intracranial meningiomas of adult NF2 patients relatively predominate in the parasagittal and convex surface regions compared with the pediatric patients. The newly developed NF2 meningiomas in adulthood are more likely to occur in the parasagittal and convex surface regions. The location patterns of intracranial meningiomas in severe-type patients are highly compatible with those in no-severe-type adult NF2 patients, showing the severe type of NF2 is most likely caused by the newly developed meningiomas in adulthood.